On the Convergence of Certain Numerical Characteristics of Variational Dirichlet Problems in Variable Domains - Kovalevskii, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We prove two theorems that enable one to reduce the problem of convergence of general characteristics of variational Dirichlet problems in variable domains to the problem of convergence of simpler characteristics of these problems. We describe the case where the convergence of simpler characteristics takes place.